1976
DOI: 10.1007/bf00673415
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sterilization in the immediate puerperium

Abstract: The safety and effectiveness of laparoscopic sterilization with electrocoagulation and separation of the tubes when performed within five days of a normal delivery is evaluated. The majority of patients (53.5%) were sterilized within 36 hours of delivery and were discharged on either the same day or the first post-sterilization day (91.0%). While some form of complications were reported for 9.5 percent of the patients, potentially serious complications occurred for only 2 patients (1.%). Most of the complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

1976
1976
1982
1982

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…T h e literature on this subject is inconclusive. Some studies have indicated that sterilization in this period does not significantly increase the complication or technical failure rates of the procedure (1,3,7), while another study has reported significantly higher complication rates (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T h e literature on this subject is inconclusive. Some studies have indicated that sterilization in this period does not significantly increase the complication or technical failure rates of the procedure (1,3,7), while another study has reported significantly higher complication rates (2).…”
Section: Discussionmentioning
confidence: 99%
“…However, since the Hulka clips were applied with a prototype laparoscope, the problems may be due to the original design of the equipment rather than being inherent in the technique. Equipment/technical problems with the prototype applicator and clips have been documented (1,5). T h e higher pregnancy rate for the spring-loaded clip is probably due in part to the greater difficulty in visualization with the single-incision applicator and in part to inadequate spring tension of some of the clips.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have found that sterilization in this period does not significantly increase the complication or technical failure rates of the procedure (4,11), while another has reported significantly higher complications (2). Many postpartum sterilizations are done by laparotomy, but laparoscopy has been demonstrated to be equally safe (1,10) and may be a good choice for the physician who wishes to apply mechanical occlusive devices to the tubes.…”
Section: Discussionmentioning
confidence: 99%
“…A higher rate of technical/equipment difficulties, primarily lens fogging, was experienced with the spring-loaded clip than with the tubal ring procedures. This has been a documented problem with the prototype clip equipment (1,3,7,12).…”
Section: Discussionmentioning
confidence: 99%
“…Selection of sterilization procedure Most postpartum sterilization procedures are performed through a small laparotomy incision and tubal occlusion is accomplished by any of several ligation techniques, usually the modified Pomeroy technique. Since laparotomy is inconvenient and often requires more than local anesthetics to achieve patient comfort, some investigators (2,4,6,11,16) have evaluated the feasibility and safety of performing laparoscopic sterilizations during the puerperium with electrocoagulation of the uterine tubes. Because laparoscopic sterilization in the postpartum period is technically more difficult, it should be performed only by surgeons with extensive experience in "interval" laparoscopic sterilization.…”
Section: Sterilization Immediately After Term Delivery (Postpartum)mentioning
confidence: 99%